Development of TiAl-Si Alloys-A Review - Knaislová, Anna; Novák, Pavel; Cabibbo, Marcello; Jaworska, Lucyna; Vojtěch, Dalibor (Materials (Basel, Switzerland), 2021)
This paper describes the effect of silicon on the manufacturing process, structure, phase composition, and selected properties of titanium aluminide alloys. The experimental generation of TiAl-Si alloys is composed of titanium aluminide (TiAl, Ti3Al or TiAl3) matrix reinforced by hard and heat-resistant titanium silicides (especially Ti5Si3). The alloys are characterized by wear resistance comparable with tool steels, high hardness, and very good resistance to oxidation at high temperatures (up to 1000 °C), but also low room-temperature ductility, as is typical also for other intermetallic materials. These alloys had been successfully prepared by the means of powder metallurgical routes and melting metallurgy methods.
Keywords: synthesis; alloy; titanium aluminide; titanium silicide; properties